Experimental Evaluation of Coffee Husk Ash as a Filler in Hot Mix Asphalt Concrete Productions - Amare Tilahun Tessema; Natnael Melsew Wolelaw; Getachew Asefa Alene (Advances in Civil Engineering)
The use of coffee husk ash (CHA) as a mineral filler in hot mix asphalt was investigated in this study. Crushed stone dust (CSD) was used as the mineral filler in four distinct serial asphalt concrete samples (5.5%, 6.5%, 7.5%, and 8%) for this purpose. The samples’ ideal bitumen content and Marshall stability (MS) value were calculated. The 6.5% filler asphalt series, which has offered the most stability, was picked, and CHA was substituted for it at rates of 25%, 50%, 75%, and 100%. The produced samples were then subjected to an MS test, and the results were evaluated. The effects of mineral filler on the susceptibility of asphalt concrete to moisture were also examined in the present study along with the preparation and evaluation of Marshall stability mixtures with various CHA and bitumen levels. The maintained stability test also evaluates a bituminous mix’s capacity to be stripped. The findings indicated that for stability, flow, air voids, VFA, and bulk density, respectively, the optimum asphalt content (5.57%) and filling rate at 75% replacement of crushed stone dust with coffee husk ash had values of 16.820 kN, 4.983 mm, 4.435%, and 73.717%. CHA can be used as long as 75% of the CSD filler material complies with the minimum standards set by the Ethiopian Road Authority and global standards for the manufacturing of hot mix asphalt concrete. The retained stability (RS) test results showed that the retained stability values increased with an increase in bitumen content, indicating that the effect of moisture damage decreases with an increase in asphalt content because a high bitumen content will have a thicker content, which reduces the tendency for the water to percolate into the asphalt mix and cause moisture-related problems.